Assessment of Wind-Related Parameters and Erodibility Potential Under Winter Wheat Canopy in Reclaimed Tidal Flat Land - Kyosuk Lee; Jaehan Lee; Kwangseung Lee; Hyunsuk Jo; Woojung Choi; Jinwoong Cho; Dougyoung Chung (Agronomy)
The aim of this study was to observe soil erosion by wind, depending on the soil physical properties, climatic conditions, and plant canopy, for three representative soil series in the reclaimed tidal flats. Soil samples were collected from the Ap horizon of three soil series to analyze soil physical properties and particle distribution. Precipitation and wind velocities were measured by the weather station installed at the filed. The particle distribution curves showed that the actual proportions of erodible soil particle were in the order of 74.7%(TH), 66.1%(PS), and 62%(JB). The instantaneous and daily maximum wind speeds exceeded the threshold friction velocity (5.78 m s−1) suggested by Chepil. However, the dynamic velocities, depending on the radius of 0.125 mm and 0.42 mm belonging to erodible particle size, were much lower than the threshold friction velocity suggested by Chepil. The wind profile increases logarithmically with height, just above the plant canopy. The vertical gradients of wind velocity for the winter wheat plot were smaller than that of the bare plot due to the relatively rough canopy, and U(Z)c of the bare plot was slightly higher than that of the winter wheat plot with a plant canopy for the given U(Z)m. Conclusively, the actual proportion of erodible particles was much less than that of the particle size limit.